Trend Analysis of Rainfall, Temperature and Relative Humidity over Kathmandu, Nepal - Regmi, A.; Sah, H.K.; Adhikari, B.; Pandit, D. (Journal of Nepal Physical Society, 2021)
Five years (2012-2016) data of Rainfall, Relative Humidity and Temperature from Tribhuvan International Airport Kathmandu, Nepal (TIA) station were analyzed. Nepal lies in the subtropical region in which experience four seasons in a year i.e., winter, spring, summer and autumn. The Mean, Correlation(r), And P-value were calculated to study the correlation between Rainfall, Relative Humidity and Temperature. Assuming the type I error alpha (α) as 5% the p-value was compared to it. T test was used to calculate the p-value. Assuming null Hypothesis (H0) to show insignificant relation between two variable and alternative hypotheses (H1) to show significant relation between two variables. The monthly analysis also shows the period of Highest Rainfall, Temperature and Relative Humidity Between June or July or August for the location of TIA Kathmandu, Nepal. The relation between Rainfall vs Relative Humidity and Relative Humidity vs temperature was found to be insignificant respectively throughout all five years. The relation between Rainfall and Temperature was found to be significant throughout all five years.